A Comparative Study of Efficacy and Adverse Effects Between Alfuzosin and Tamsulosin in the Treatment of Benign Prostatic Hyperplasia (Ibrahim Cardiac Medical Journal, 2011)
Keywords: Tamsulosin, alfuzosin; lower urinary tract symptoms; benign prostatic hyperplasiaIbrahim Card Med J 2011; 1(1):27-32